Toxicological Assessment of a Standardized Boswellia serrata Gum Resin Extract. (September 2019) - Alluri, Venkata Krishnaraju; Dodda, Sundararaju; Kilari, Eswar Kumar; Golakoti, Trimurtulu; Sengupta, Krishanu
The acidic and non-acidic fractions of Boswellia serrata gum resin extracts were combined to prepare a unique product, LI13019F1 (Serratrin). The present series of studies evaluated LI13019F1 for acute and subchronic (28-day) toxicity in Wistar rats and acute dermal and eye irritation in New Zealand white rabbits. The mutagenicity and clastogenicity of LI13019F1 were evaluated in bacteria and mouse bone marrow erythrocytes, respectively. All studies were performed following the Organization for Economic Co-operation and Development guidelines. Acute oral and acute dermal toxicity studies did not show mortality or signs of toxicity in Wistar rats at a limit dose of 2, 000 mg/kg LI13019F1. LI13019F1 did not cause irritation to the skin or the eyes of New Zealand white rabbits. In a repeated dose 28-day oral toxicity study, LI13019F1-treated Wistar rats did not show dose-related signs of toxicity on their body weights, organ weights, and on the hematology and clinical chemistry parameters. The estimated no observed adverse effect level for LI13019F1 was 1, 000 mg/kg/day in both male and female rats. The bacterial reverse mutation test and a micronucleus assay in mouse bone marrow erythrocytes revealed that LI13019F1 was neither mutagenic nor clastogenic. Together, the present observations demonstrate a broad-spectrum safety of LI13019F1.